2020
DOI: 10.1136/bmjopen-2020-040151
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Surveillance vs. Anticoagulation For low-risk patiEnts with isolated SubSegmental Pulmonary Embolism: protocol for a multicentre randomised placebo-controlled non-inferiority trial (SAFE-SSPE)

Abstract: IntroductionThe clinical significance of subsegmental pulmonary embolism (SSPE) is currently unclear. Although growing evidence from observational studies suggests that withholding anticoagulant treatment may be a safe option in selected patients with isolated SSPE, most patients with this condition receive anticoagulant treatment, which is associated with a 90-day risk of recurrent venous thromboembolism (VTE) of 0.8% and major bleeding of up to 5%. Given the ongoing controversy concerning the risk-benefit ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 72 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…A larger cohort study is limited due to the heterogeneity in data collection and management guidelines across different district health boards in New Zealand. The Clinical Surveillance vs. Anticoagulation for Low‐risk Patients with Isolated Subsegmental Pulmonary Embolism (SAFE‐SSPE) study, the first randomised control trial on the management of SSPE patients, is currently enrolling patients and will hopefully be providing some important evidence‐based guidance 11 . Second, minor bleeding or asymptomatic thrombotic events might be under‐reported either due to recollection errors or missing clinical documentation.…”
Section: Discussionmentioning
confidence: 99%
“…A larger cohort study is limited due to the heterogeneity in data collection and management guidelines across different district health boards in New Zealand. The Clinical Surveillance vs. Anticoagulation for Low‐risk Patients with Isolated Subsegmental Pulmonary Embolism (SAFE‐SSPE) study, the first randomised control trial on the management of SSPE patients, is currently enrolling patients and will hopefully be providing some important evidence‐based guidance 11 . Second, minor bleeding or asymptomatic thrombotic events might be under‐reported either due to recollection errors or missing clinical documentation.…”
Section: Discussionmentioning
confidence: 99%
“…This compares with 5.3% VTE recurrence, 8.1% bleeding, and 2.1% mortality for the anticoagulation treated SSPE patients in the Bariteau et al, meta-analysis [10]. However, the studies included in this meta-analysis were heterogenous with many lacking Pulmonary Embolism) [34,35] to address this important question.…”
Section: Radiological Findingsmentioning
confidence: 95%
“…The management of subsegmental PE in particular remains controversial. Although there is growing evidence that not anticoagulating patients with subsegmental PE is a safe approach, the data is mainly from patients without malignancy [ 23 , 24 ]. One study of cancer patients reported that whilst symptomatic PE showed better survival with anticoagulation, anticoagulation did not result in significant survival benefit in IPE.…”
Section: Anticoagulation Strategy In Ipementioning
confidence: 99%